The study of physicochemical properties of the sedimentary chalk surface of domestic deposits - Аршинніков, Дмитро Ігорович; Свідерський, Валентин Анатолійович (Eastern-European Journal of Enterprise Technologies, 2015)
The physicochemical properties of the surface of sedimentary chalk deposits in Ukraine were studied, quantification of wettability in static cycles (water) with sinters (water and xylene) compared to chemically precipitated chalk and some imported varieties of calcite was presented. The importance of the role of mineralogical composition and content of adsorbed water in the process of implementation of polar and nonpolar wetting liquids is shown. The effect of specific surface area, particle morphology, pore structure, surface energy state and variety of sedimentary varieties on the wetting process and adsorption activity with respect to water and oil was evaluated. Analysis of the importance of the role of chemically deposited chalk in the above-mentioned processes was also conducted. The influence of hydrophobication of calcium carbonates on sedimentary chalk, for example, the possibility of a fundamental change in the physicochemical properties of the surface was analyzed. Future possibilities for use of natural sedimentary chalk in the finished building materials suitable for various functional applications were identified.